A daily diary investigation of self‐reported alcohol‐related direct and indirect aggression. Issue 4 (1st April 2019) - Sheehan, Brynn E.; Lau‐Barraco, Cathy
Abstract: Research supports the relationship between alcohol use and direct aggression, however, scant research has examined the association between alcohol use and indirectly aggressive behavior. Further, extant research has relied on retrospective reporting of behaviors, which may be subject to recall bias. The daily diary methodology enables the assessment of both the between‐ and within‐subject variation, as well as reduces the likelihood of biased reporting. Consequently, the current study utilized a daily diary design to examine (a) associations between daily alcohol use and alcohol‐related aggressive behaviors (i.e., direct and indirect); and (b) the co‐occurrence of alcohol‐related direct and indirect aggression. Participants were 105 (80% female) college student drinkers. Students completed baseline questionnaires and up to 14 consecutive, daily surveys regarding their previous day alcohol use, alcohol‐related direct aggression, and alcohol‐related indirect aggression. Findings revealed that alcohol use was associated with same day alcohol‐related direct and indirect aggression, after controlling for baseline alcohol use. Self‐reported alcohol‐related direct aggression was more likely to occur on days in which self‐reported alcohol‐related indirect aggression occurred, after controlling for dispositional aggression, trait self‐control, and baseline alcohol use. Results of the study suggest that, similar to alcohol‐related direct aggression, alcohol use is associated with an increased likelihood of alcohol‐related indirect aggression. Further, the co‐occurrence of alcohol‐related indirect and direct aggression supports that individuals may be engaging in multiple types of aggressive behaviors. Findings extend previous cross‐sectional and qualitative research suggesting that indirect aggression may co‐occur, perhaps increasing in severity.